The ICJ and Multi-forum Litigation Strategy - Voulgaris, Nikolaos, (International Law E-books Online, Collection 2026., 2025)
In a world where inter-State multi-forum litigation multiplies, so does the risk of courts becoming diplomatic platforms to air State grievances. Nowadays, the ICJ is called to confront this risk when dealing with the main political issues of the day. The book draws inferences from legal and political sciences to assess ICJ authority when crises make their way to it as part of a multi-forum litigation strategy. It identifies the essential characteristics of this strategy and delineates ICJ instrumentalization against this background. Three running examples expose the many roles implanted in the ICJ when it is so instrumentalized. And they determine the legal and policy ramifications ensuing from a State's attempt to engage in such a judicial-'diplomatic' campaign.